Impacts of clinical research units on clinical research — a systematic review of empirical studies - Wang, Fan; Wang, Xu; Liu, Enmei; Song, Fujian; Chen, Yaolong (Systematic reviews, 2025)
Clinical research is essential for evidence-based decision-making in healthcare practice, but its conduct is hindered by various barriers. While previous studies suggest that clinical research units (CRUs) provide critical support and expertise for complex clinical research, their necessity for ensuring high-quality clinical research remains uncertain. The primary objective of this systematic review is to identify, assess, and summarize results of studies that empirically evaluated the impacts of CRUs on clinical research. We conducted a comprehensive search of PubMed, Embase, Web of Science, and ProQuest Dissertations and Theses Global from inception to July 2024 to identify relevant studies. Study selection, quality evaluation, and data extraction were performed independently by two reviewers, with any disagreements resolved through discussion. Data extracted from the included studies were summarized in tables, and the synthesis were guided by a realist review approach. A total of 11 publications corresponding to 10 studies were included in the review. These studies involved 8 independent CRUs and 2 groups of CRUs. The settings in the CRUs operated were diverse, including general hospitals or medical centres, paediatric hospitals, professional sarcoma group, and others. The CRUs featured varied structures and staff compositions, with services tailored to the specific needs of local research teams, study types, and the availability of other research resources. The reported impacts of CRUs were consistently positive in terms of efficiency, quantity, and quality of clinical research. Following the establishment of the CRUs, the number of clinical research has increased by 5 to 23 annually. The implementation of CRU enhances the efficiency, quantity, and quality of clinical research through process refinement, methodological support, resource pooling, reduced researcher workload, and adherence to good clinical practice (GCP), thereby ensuring patient safety and data integrity. Future research should include rigorous comparative studies, such as randomized controlled trials (RCTs) comparing outcomes with and without CRUs, to further validate these findings. PROSPERO CRD42024575392.